2022
DOI: 10.3389/fmars.2022.814233
|View full text |Cite
|
Sign up to set email alerts
|

Spray-Dried Porcine Plasma Promotes the Association Between Metabolic and Immunological Processes at Transcriptional Level in Gilthead Sea Bream (Sparus aurata) Gut

Abstract: The spray-dried porcine plasma (SDPP) is an abattoir by-product used in animal nutrition with beneficial effects reported in livestock and commercial aquatic species. Previous results have found that the dietary inclusion of SDPP in gilthead sea bream (Sparus aurata) increased the density of intestinal goblet cells, and it did not result in significant changes in the autochthonous microbiota. However, there is no comprehensive data on the mechanisms that could take place on the intestine of gilthead sea bream … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 79 publications
(120 reference statements)
2
6
0
Order By: Relevance
“…In addition, the beneficial effects on skin mucus in response to protein hydrolysates had also been confirmed in meagre [ 19 ] and seabream [ 14 , 18 ], benefits that could be imputed to the bioactive compounds existing in SDPP, such as growth factors, albumins, immunoglobulins, and biological active peptides, which may moderate the immunomodulatory and anti-inflammatory effects [ 64 , 65 ]. These dietary systemic and mucosal effects confirmed the prior evidence of the metabolic, immune, and protein transport processes that occur in response to SDPP at the mucosal tissue level [ 15 , 18 ]. In similar studies conducted by Vallejos et al [ 15 ] and Reyes-López et al [ 18 ], SDPP was tested at higher levels of FM inclusion (47%), and the results from the above-mentioned studies indicated a remarkable association between immunity, protein transport, and metabolic-associated processes in response to the SDPP diet.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…In addition, the beneficial effects on skin mucus in response to protein hydrolysates had also been confirmed in meagre [ 19 ] and seabream [ 14 , 18 ], benefits that could be imputed to the bioactive compounds existing in SDPP, such as growth factors, albumins, immunoglobulins, and biological active peptides, which may moderate the immunomodulatory and anti-inflammatory effects [ 64 , 65 ]. These dietary systemic and mucosal effects confirmed the prior evidence of the metabolic, immune, and protein transport processes that occur in response to SDPP at the mucosal tissue level [ 15 , 18 ]. In similar studies conducted by Vallejos et al [ 15 ] and Reyes-López et al [ 18 ], SDPP was tested at higher levels of FM inclusion (47%), and the results from the above-mentioned studies indicated a remarkable association between immunity, protein transport, and metabolic-associated processes in response to the SDPP diet.…”
Section: Discussionsupporting
confidence: 80%
“…As it has been previously stated, functional feeds are commonly used to modulate the immune and stress responses; however, predicting functional response is very difficult due to complex interactions between dietary ingredients [ 33 ]. Although there are benefits of SDPP in terms of growth, feed efficiency and host’s immunity in diets formulated with high levels of FM (46%) [ 13 , 15 , 18 ], there is not information on whether low FM diets (2%), such as those tested in the current study and in our previous studies [ 14 ], would behave similarly to full FM ones. Thus, in this study, the authors aimed to evaluate the potential immunomodulatory effect of SDPP inclusion in diets with very low levels of FM (2%) by means of an ex vivo assay.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations